BTS Fan’s Register in BTS Official Instagram Account - Yustisiana, Rr. Arielia; Cahyanti, Elok Purnama (English Teaching Journal : A Journal of English Literature, Language and Education, 2023)
BTS stands for Bangtan Boys which is Bangtan Sonyeondan in Korean. It is a famous Korean boyband. Because of their worldwide fame, they have many fans from all around the world. With their different languages, the fans as known as ARMY accidentally produced register. There were certain words and phrases produced when they wrote comments in the comment section of BTS’ official Instagram account. BTS became one of the most popular boy groups in the world. Their Instagram account was followed by 69.8 million people in the world so that there are many registers were created through the comment section and it became interesting. The research aimed to find out the types of registers, linguistic forms of registers, and meaning of registers used by BTS fans on BTS's official Instagram account. The qualitative descriptive research method is used because it was appropriate to describe the register phenomenon with a common meaning and particular meaning. The finding showed that the register is divided into six types including BTS' Agency, BTS’ Nickname, BTS’ Show, BTS’ Song, BTS’ Tagline, and K-Pop Nickname. The most dominant type of register is BTS’ Nickname because their fans created many nicknames for BTS’ members. The type that is not frequently found is BTS’ Agency because BTS only works in two agencies. The dominant linguistic form found in the research was compounding because the unique culture of BTS makes BTS fans use various terms in compounding form. On the contrary, the verb is rarely found because verbs are only used to create taglines. Depending on the context, BTS fan registers have different meanings.